Cannabidiol use among elite-level Canadian athletes: the pursuit of improved sleep, pain relief, and enhanced recovery - Karam, Dimitri; Sesbreno, Erik; Drager, Kelly; Boegman, Susan; Duncan, Lindsay R.; Jensen, Dennis; Churchward-Venne, Tyler A. (Frontiers in Nutrition, 2025)
IntroductionCannabidiol (CBD) is a compound in the cannabis plant with psycho-physiological effects that may support athletes’ training and recovery. Although not banned by the World Anti-Doping Agency, CBD products may carry a risk of inadvertent anti-doping violations due to contamination with prohibited cannabinoids. The primary objective of this study was to characterize the use, rationale, and perceived benefits of CBD use by elite-level athletes in Canada. The secondary objectives were to (1) identify the sources of information that influence CBD use, (2) describe how athletes are using CBD, and (3) explore the barriers or deterrents to its use.DesignCross-sectional descriptive survey study.MethodsElite-level Canadian athletes completed an anonymous online survey on CBD use between October 2021–June 2023.Results80 athletes completed the survey. 38% (n = 30) had used CBD, with 30% (n = 9) of CBD users reporting active/current use. CBD users cumulatively agreed or strongly agreed that CBD is safe (96%); improved sleep (93%) and relaxation (90%); and reduced pain from training (77%). Friends (26%) and the internet (24%) were the most frequently reported first sources of information on CBD. Oral tincture/oil was the most commonly used (31%) form of CBD. The most reported reason for never using or discontinuing CBD was concern about an anti-doping rule violation (28%).DiscussionGiven the self-reported benefits of CBD among elite-level Canadian athletes, alongside concerns about inadvertent anti-doping violations, clinicians working with this population should provide evidence-based guidance on CBD use and support informed decision-making to minimize risk and optimize athlete safety.